2019
DOI: 10.1016/j.jobcr.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ki-67, p53, α-SMA and COX-2 in lichen planus and related lesions: A pilot study

Abstract: Background: Researchers have struggled to understand the natural history of lesions presenting with both lichenoid features and epithelial dysplasia. Thus the present study was designed to differentiate between OLP, OLP with dysplasia, epithelial dysplasia and epithelial dysplasia with lichenoid features based on the expressions of ki-67, p53, COX-2, and α-SMA. Materials and methods: Formalin-fixed paraffin-embedded archival specimens of OLP, OLP with dysplasia, epithelial dysplasia and epithelial dysplasia wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…Nonetheless, many biomarkers expressed in OLP are also overexpressed in OSCC 8 , 20 . The correlation between HSP90 expression, low E-cadherin expression and disease duration for OLP patients observed in this study are partly consistent with previous reports, which suggests that in cases of long disease duration, the risk of genetic changes may be increased 6 , 7 , 20 . In our study, HSP90 expression was more frequently observed in non-erosive OLP, but it was limited to small tissue areas, and this type of OLP is associated with longer disease duration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nonetheless, many biomarkers expressed in OLP are also overexpressed in OSCC 8 , 20 . The correlation between HSP90 expression, low E-cadherin expression and disease duration for OLP patients observed in this study are partly consistent with previous reports, which suggests that in cases of long disease duration, the risk of genetic changes may be increased 6 , 7 , 20 . In our study, HSP90 expression was more frequently observed in non-erosive OLP, but it was limited to small tissue areas, and this type of OLP is associated with longer disease duration.…”
Section: Discussionsupporting
confidence: 92%
“…The association between the p53 protein and the areas of oral mucosa observed in non-erosive OLP in this study is in line with the observations of Shiva et al 22 , who observed p53 protein expression in non-erosive OLP. The results of this study, which show increased p53 and HSP90 expression and lower E-cadherin expression in OSCC in comparison to OLP are in line with other data indicating that dysfunctions of these proteins may lead to malignant lesions in some cases 6 , 7 , 10 , 11 . The impact of these proteins on the aggressive biological behaviour of OLP lesions is reflected in our data, which shows their increased expression in OSCC, as well as a correlation with worse clinical and pathological features of tumours.…”
Section: Discussionsupporting
confidence: 92%
“…Of the 5 included studies ( 5 , 7 - 10 ), two were from India ( 7 , 9 ), one from Canada ( 5 ), one from Australia ( 8 ) and one from Iran ( 10 ). The various diagnosis rendered among these 181 cases included OLD (n=73); OLP with epithelial dysplasia/dysplastic OLP (n=19); oral lichenoid mucositis (OLP or OLL) with epithelial dysplasia (n=73); OLL with dysplasia (n=16).…”
Section: Resultsmentioning
confidence: 99%
“…Oral mucosal lesions presenting with both lichenoid and epithelial dysplastic features are often misdiagnosed. The cause for the misdiagnosis in most of these cases is due to the difficulty in identifying the primary pathology and the lack of universally accepted diagnostic criteria ( 1 - 4 , 7 , 9 ). The present review analyses the varied spectrum of clinicopathological features and diagnoses rendered in original studies investigating oral mucosal lesions with both lichenoid and epithelial dysplastic features.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inflammation is strongly associated with carcinogenesis, including the development and progression of oral cancer [33] [34]. Further, COX-2 expression has been correlated with higher grades of oral epithelial dysplasia and could represent an early event in oral carcinogenesis [35] [36]. Several studies, including that of Arreaza, et al [32], found a higher COX-2 expression in OLP than in OLLs, and Chankong, et al [37] observed a direct correlation between COX-2 expression in OLP and the clinical severity of this pathology.…”
Section: Discussionmentioning
confidence: 99%